The Odyssey : Homer. - SparkNotes LLC (SparkTeach, 1997)
"Whether you're teaching in the classroom, facilitating remote learning, or homeschooling, you'll find SparkTeach guides will engage your students in one of the world's most important works of literature. Lesson plan materials, worksheets, projects, discussion questions, and more are all rolled into one comprehensive guide. Each SparkTeach guide contains: dozens of lesson activities aligned to Common Core State Standards; Real-Life Lens Lesson plans that help readers explore the work's key themes through a relatable lens; dynamic projects for students to display mastery of the text in creative ways; Poetics Lessons to help students explore literary devices; suggestions for differentiated instruction; reproducible worksheets and assessments that build reading, vocabulary, and critical-thinking skills; answer keys and a rubric for student assessment. Also included are tips for class planning and management, dozens of ideas for personalizing content, and more."